Faktor-Faktor yang Memengaruhi Kualitas Laporan Keuangan Pemerintah Kabupaten Rokan Hilir - Siska Vadila; Taufeni Taufik; Yesi Herawati (Owner : Riset dan Jurnal Akuntansi, 2026)
The quality of local government financial reports reflects the accountability of public financial management. However, the quality of financial reporting in Indonesia is still not optimal, as indicated by the Local Financial Management Index (IPKD) and audit findings issued by the Supreme Audit Agency (BPK), especially in Rokan Hilir Regency. This condition shows the need to identify key factors that affect the quality of local government financial reports. This study aims to test and prove the influence of human resource competence, internal control systems, follow-up on BPK audit results, and the utilization of information technology on the quality of financial reports. This study uses a quantitative approach. The population in this study was all regional apparatus organizations (OPD) in Rokan Hilir Regency. The sampling technique used was purposive sampling, resulting in 26 OPDs as research samples with a total of 78 respondents. The type of data used was primary data obtained through the distribution of questionnaires to respondents. The collected data was then analyzed using SmartPLS software version 4.1.1.4. The results showed that human resource competence, internal control systems, follow-up on BPK audit results, and the utilization of information technology had an effect on the quality of financial reports. This study concluded that internal organizational factors and technological support played an important role in improving the quality of local government financial reports, particularly in OPDs in Rokan Hilir Regency.